Bacteria and fungi analyses of fish diets with grasshopper and cockroach meals: the potential replacement of fishmeal in fish diets - Adamu, Kabir Mohammed; Aliyu-Paiko, Mohammed; Mohammed, Yakubu Manbe; Adebola, Taofikat Tinuola; Hafsat, Muhammad; Iloba, Kate Isioma (Journal of Fisheries, 2022)
The need to further ascertain the quality of fishmeal with biological indicators has poised this study to determine the biological characterisation of formulated diets with supplemented insect protein (variegated grasshopper and American cockroach). The diets (A–F) were prepared with local ingredients (A, 100% grasshopper meal; B, 100% fishmeal; C, 1:1 grasshopper:fishmeal; D, 1:1 cockroach:fishmeal; E, 100% cockroach meal; F, commercial diet). Samples of prepared diets ready to be stored for use were subjected to bacteria and fungi test. Diet F recorded the highest (4.60±1.10×102 cfu g–1) total viable bacteria count. The highest (3.00±0.05×102 cfu g–1) fungi count was recorded in diet A. Six probiotics bacteria were isolated from the diets. Lactobacillus delbrueckii subsp. bulgaricus was only isolated in grasshopper containing diets; as Pediococcus pentosaceus, Bifidobacterium longum, Mycobacterium marinum, Bacillus subtilisand, Lactococcocus lactis were only isolated in diets F, E, D, A and B respectively. Two pathogenic bacteria isolated were Streptoccoci pyogenes and Staphylococcus aureus. Aspergillus flavus and Penicillum sp. are the two species of fungi isolated from diet A, and diets C and E respectively. The diets with insect proteins were rich in probiotic bacteria than other diets may be considered to replace fishmeal in fish diet.